Pengembangan Pengembangan Perangkat Pembelajaran Digital Berbasis ICARE untuk Meningkatkan Kemampuan Pemecahan Masalah dan Efikasi Diri - Cahyani, Ni Putu Candra; I Nengah Suparta; I Gusti Putu Suharta (JPG: Jurnal Pendidikan Guru, 2024)
This study aims to produce characteristics of digital learning devices and characteristics of the implementation of learning devices based on the ICARE model in improving students' mathematical problem solving ability and self-efficacy. This design research uses Plomp's research procedures. The product trial used the shifting method. The research subjects were students of class XA (limited trial), XC (field test I), and XE (field test II) at SMAN 1 Blahbatuh. The data collected from the research instruments were analyzed descriptively. The research results in the form of digital learning devices including teaching modules, digital student books, problem solving tests, and student self-efficacy questionnaires that are valid, practical, and effective. Validity uses expert test. Practicality uses the implementation sheet, student and teacher response questionnaires. Effectiveness using problem solving tests and student self-efficacy questionnaires at each meeting. The characteristics of the device obtained are digital; focus on improving students' math problem solving skills and self-efficacy; use the ICARE model; integrate technology; pay attention to the diversity of learning styles; self-efficacy questionnaire that can open students' minds; math problem solving test